Quantification of fluoroquinolones in wastewaters by liquid chromatography-tandem mass spectrometry - Maia, Alexandra S. (2020)
Antibiotics are the most consumed therapeutic classes worldwide and are released to the environment in their original form as well as potentially active metabolites and/or degradation products. Consequences of the occurrence of these compounds in the environment are primarily related to bacterial resistance development. This work presents a validated analytical method based on solid phase extraction (SPE) using HLB cartridges, followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) for quantification of seven different fluoroquinolone antibiotics, namely ciprofloxacin (CPF), enrofloxacin (ENR), lomefloxacin (LOM), norfloxacin (NOR), ofloxacin (OFL), prulifloxacin (PLF) and moxifloxacin (MOX) and its application to detect the target compounds in influents and effluents of wastewater treatment plants (WWTP). Linearity was established through calibration curves in solvent and matrix match using internal calibration method in the range of 50–1300 ng L−1 and all the fluoroquinolones showed good linear fit (r2 ≥ 0.991). Accuracy ranged between 80.3 and 92.9%, precision was comprised between 7.2 and 14.6%, and 10.7 and 18.1% for intra- and inter-batch determinations, respectively. Method detection and quantification limits ranged from 6.7 to 59.0 ng L−1 and 22.3–196.6 ng L−1, respectively. Influents and effluents of fifteen WWTPs of North of Portugal were analyzed. OFL was the fluoroquinolone found at the highest concentration, up to 4587.0 ng L−1 and 987.9 ng L−1, in influent and effluent, respectively. NOR and PLF were not detected.